Evaluation of in-house loop-mediated isothermal amplification for tuberculosis diagnosis compared with Xpert MTB/RIF - Charity Habeenzu; Chie Nakajima; Eddie Solo; Precious Bwalya; Kiichi Kajino; Mari Miller; Youichi Kurosawa; Victor Mudenda; Lackson Kasonka; Yasuhiko Suzuki; Takashi Matsuba (Journal of Infection in Developing Countries)
Introduction: To evaluate the diagnostic performances of an in-house loop-mediated isothermal amplification (LAMP) kit and the Xpert MTB/RIF test for the diagnosis of pulmonary tuberculosis in a resource-limited setting, this study was performed at the University Teaching Hospital, Ministry of Health, the Republic of Zambia.